An Analysis of the Entry Barriers for Firms entering the Indian Market. A case for the Crude Oil and Fertilizer Industry. - Eapen, John (2011)
International businesses are seeking opportunity to expand their business in emerging markets. Globalization has provided opportunities to enter new markets and access untapped resource. This has resulted is flourishing of trade between countries. In the process on internationalization firm are undergoing difficulties is using the same methods used in the home countries to enter new markets. This results in losses for the firm and even business failure. This report is based on the analysis of the crude oil and the fertilizer industry. The market study is done to understand the attractiveness of the industry and the fundamental characteristics of the market. With the help of PESTEL and The Five Forces models the report analyses the external and internal barriers of the industry and the interventions like corruption that would also impact the industry. With the help of Internationalization models the report suggests possible internationalization processes that a new entrant could use to enter the Indian market. The main focus of the report is to analyses the barriers that new entrants face in the new market entry. By exploring the different barriers in the market firms will be able align their strategies depending on the possible barriers. It also focuses on the governmental interventions and corruption which underlie in the system. To gain competitive advantage firms need to factor in these barriers and formulate a strategy to internationalize.